Controle parcial de potência em sistemas de energia através de um transformador de estado sólido híbrido - Del Piero, Fádua Cozac Gonçalves (2024)
In recent years, there has been an increasing focus in science on engineering to optimize components and systems, driving advances in semiconductor technology in power electronics. This has enabled the use of higher switching frequencies, reduced volume, and increased efficiency. Within this context, microgrids, which rely on transformers and converters to integrate sources, loads, and systems, are gaining prominence. With the growing adoption of distributed energy sources, especially renewables, the use of efficient converters to control voltage, current, and power flow becomes crucial. However, the limitations of conventional transformers, such as limited voltage control and large volume, restrict system optimization. An alternative is the Solid-State Transformer, which offers advantages such as reactive power compensation, voltage regulation, and reduced size. Despite these benefits, the implementation of the Hybrid Solid State Transformer faces challenges, such as higher cost and lower efficiency. To overcome these difficulties, a hybrid topology is proposed that combines the conventional transformer with the Solid-State Transformer. In this work, a hybrid system was developed that uses the Solid-State Transformer for partial energy control, while the conventional transformer performs most of the transformation. Additional functionalities such as parallel and series active filters, reactive compensator, and dynamic voltage regulator were implemented. The system was analyzed under various load and supply profiles to validate the proposed topology and control, thereby demonstrating the feasibility of the configuration for a real-world situation